Effect of seed size on some germination characteristics of three bread wheat (Triticum aestivumL.) cultivars - عباس زارعیان; حسین حیدری شریف آباد; لیلا یاری; بیتا اسکویی (علوم و فناوری بذر ایران, 2012)
Among the production factors, seed as the primary production factor plays an important role in the transfer and exploitation of genetic characteristics seeds aiming to increase qualitative and quantities of the yield. Among growth stages of plants, seed germination and emergence stages are the most critical growth stages and play a pivotal role in plant establishment in fields. In order to investigate the impacts of seed diameter size on characteristics of germination in three wheat )Triticum aestivum L.( cultivars, this study was conducted in 2008 in a research station of seed and plant certification and registration research institute, Karaj, Iran. The experimental factors were five seed diameters ) 2-2.2, 2.2-2.5, 2.5-2.8, 2.8-3 ,andgt;3 mm ( and three wheat cultivars )Mahdavi, Pishtaz and Bahar(. In laboratory, seeds from different size class from cultivars were planted in a completely randomized design with 3 replicates. Germination percentage, germination speed , seedling-length, radicle-length, plumule-length, seedling dry weights, radicle dry weights and plumule dry weights were measured. Data analysis showed that seed size had a significant impact on speed of germinations, radicle dry weights, plumule dry weights and seedling dry weights. Results indicated that germination speed significantly decrease with increasing seed size. The other traits showed significant increases with increasing seed size. Cultivar had significant impact on germination characteristics but germination percentage and germination speed were similar between cultivars. Mahdavi cultivarandrsquo;s seedling length and dry weight was dependent on 1000 number of seed weights, especially influenced by 2.5-2.8, 2.8-3 and andgt;3 mm seed diameter, Seed size may be equivalent to the amount of nutrients saved in seeds. Therefore larger seeds may produce vigorous seedlings. Significant interaction was observed for radicle-length, plumule-length and seedling dry weight. This study suggested that the wheat genotypes did not have similar performance regarding to the variation in seed sizes .